2014
DOI: 10.1186/1471-230x-14-135
|View full text |Cite
|
Sign up to set email alerts
|

The added value of using mutational profiling in addition to cytology in diagnosing aggressive pancreaticobiliary disease: review of clinical cases at a single center

Abstract: BackgroundThis study aimed to better understand the supporting role that mutational profiling (MP) of DNA from microdissected cytology slides and supernatant specimens may play in the diagnosis of malignancy in fine-needle aspirates (FNA) and biliary brushing specimens from patients with pancreaticobiliary masses.MethodsCytology results were examined in a total of 30 patients with associated surgical (10) or clinical (20) outcomes. MP of DNA from microdissected cytology slides and from discarded supernatant fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Unlike FISH which relies on the presence of intact neoplastic cells in the specimen, other studies focused on DNA mutation analysis using the residue supernatant fluid after cytocentrifugation of brushing specimens . In a recent prospective study of 100 patients (41% had biliary malignancies), KRAS oncogene and tumour‐suppressor gene loss‐of‐heterozygosity mutations were tested along with FISH and cytology.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike FISH which relies on the presence of intact neoplastic cells in the specimen, other studies focused on DNA mutation analysis using the residue supernatant fluid after cytocentrifugation of brushing specimens . In a recent prospective study of 100 patients (41% had biliary malignancies), KRAS oncogene and tumour‐suppressor gene loss‐of‐heterozygosity mutations were tested along with FISH and cytology.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the multitude of biomarkers requested, the limited volume tissue available on the cytology slides may not always be adequate. Recent studies have shown that substantial amounts of nucleic acid can be retrieved from the supernatant fluid of fine needle aspiration needle rinses after centrifugation and cell pelleting [23][24][25][26][27]. In routine clinical workflow, this supernatant fluid is typically discarded; however tumor DNA that may be left in this fluid can be effectively utilized for characterizing molecular changes in tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using supernatant fluid of pancreatic fine needle aspiration samples fixed in Saccomano's fixative, have shown that adequate and amplifiable DNA can be extracted for KRAS (codon 12 and 13) mutation analysis by pyrosequencing [23][24][25][26], even when the cellular content (smears) from the corresponding cytology sample lacked sufficient cellularity [24]. Another recent study using thyroid fine needle aspiration samples reported the detection of BRAF mutations by pyrosequencing using supernatants from aspirates collected in CytoLyt [27].…”
Section: Introductionmentioning
confidence: 99%
“…12 Postcentrifuged supernatant fluid from FNA needle rinses has been known to yield substantial amounts of DNA that are sufficient for assays such as microsatellite fragment analysis for loss of heterozygosity as well as hotspot-based mutational analysis by PCR/capillary electrophoresis and pyrosequencing. [13][14][15][16][17] A recent study by our group demonstrated that supernatant fluid samples from FNA needle rinses can provide adequate DNA for NGS and droplet digital PCR to provide clinically relevant genomic information for a variety of solid tumors, including lung carcinoma, melanoma, and colorectal adenocarcinoma. 18 Furthermore, another recent study has demonstrated the feasibility of using supernatant DNA fluid from patients with lung cancer for tumor genotyping by mutational analysis.…”
mentioning
confidence: 99%